Cultural cognition of the risks and benefits of nanotechnology - Kahan, Dan M.; Braman, Donald; Slovic, Paul; Gastil, John; Cohen, Geoffrey (Nature nanotechnology, 2009)
How is public opinion towards nanotechnology likely to evolve? The ‘familiarity hypothesis’ holds that support for nanotechnology will likely grow as awareness of it expands. The basis of this conjecture is opinion polling, which finds that few members of the public claim to know much about nanotechnology, but that those who say they do are substantially more likely to believe its benefits outweigh its risks 1 , 2 , 3 , 4 . Some researchers, however, have avoided endorsing the familiarity hypothesis, stressing that cognitive heuristics and biases could create anxiety as the public learns more about this novel science 5 , 6 . We conducted an experimental study aimed at determining how members of the public would react to balanced information about nanotechnology risks and benefits. Finding no support for the familiarity hypothesis, the study instead yielded strong evidence that public attitudes are likely to be shaped by psychological dynamics associated with cultural cognition. A sample of 1,862 adults was presented with balanced information on the risks and benefits of nanotechnology. Subjects did not react in a uniform manner, but polarized along lines consistent with cultural predispositions towards technological risk generally.